Korzet pro léčení skoliózy: vývoj našeho korzetu od roku 1970. Hodnocení normalizace rotace, statiky žeber a klínovitého tvaru obratlů - Cheneau, Jacques (Pohybové ústrojí. Pokroky ve výzkumu, diagnostice a terapii, 2003)
After having shortly presented Abbott, a genious, the first one who could cure scoliosis, and briefly described the main principles of bracing and the way the other schools are bracing now, the authors present the model that one of them has conceived. It is build with polyethylene. Fifty four zones are taken in account on the scoliosis body.Wide and deep spaces must be managed on concave areas. It has to be adjusted to patient,immediately after delivery, regularly during the duration of a brace and occasionally if necessary. The height, width and breadth as well as many details can be adjusted at least as well as in all other methods. Nine kinds of mechanisms, 4 active and 5 passive, contribute altogether to the correction of scoliosis. A series of short term results is presented, where angle according to Cobb, rotation, rib static and wedge shape are evaluated. All those features had got an average bettering of 41 to 60 %.
Keywords: ortopedické fixační pomůcky; Scoliosis; protetické prostředky; Orthopedic Fixation Devices; zakřivení páteře; výztuhy; skolióza; Humans; Ribs; lidé; Braces; Outcome and Process Assessment, Health Care; Spinal Curvatures; žebra; výsledky a postupy - zhodnocení (zdravotní péče); Orthotic Devices